Participation of Short-Chain Fatty Acids and Their Receptors in Gut Inflammation and Colon Cancer - Carretta, María Daniella; Quiroga, John; López, Rodrigo; Hidalgo, María Angélica; Burgos, Rafael Agustín (Frontiers in Physiology, 2021)
Short-chain fatty acids (SCFAs) are the main metabolites produced by the bacterial fermentation of dietary fiber, and they play a critical role in the maintenance of intestinal health. SCFAs are also essential for modulating different processes, and they have anti-inflammatory properties and immunomodulatory effects. As the inflammatory process predisposes the development of cancer and promotes all stages of tumorigenesis, an antitumor effect has also been associated with SCFAs. This is strongly supported by epidemiological studies showing that a diet rich in fiber is linked to a reduced risk of colon cancer and has significant clinical benefits in patients with inflammatory bowel disease (IBD). SCFAs may signal through the metabolite-sensing G protein-coupled receptors free fatty acid receptor 3 [FFAR3 or G protein-coupled receptor 41 (GPR41)], FFAR2 (GPR43), and GPR109A (also known as hydroxycarboxylic acid receptor 2 or HCAR2) expressed in the gut epithelium and immune cells. This review summarizes the existing knowledge regarding the SCFA-mediated suppression of inflammation and carcinogenesis in IBD and colon cancer.